A justiça reprodutiva como instrumento de promoção da autonomia reprodutiva de mulheres negras no Brasil - Isa Carla Alves de Souza (2023)
This work intends to demonstrate that the liberal and universalizing conception in which reproductive rights were legally constituted are insufficient to guarantee effective protection to black women in Brazil. The starting point was the the finding that reproductive rights include the right that individuals have to decide about their reproductive events, to decide if, when, how, with whom or how many children they want to have. These rights also include the State's duty not to interfere in this decision and provide the means for people to carry out their reproductive projects. However, from Foucault's perspective, the sexuality device linked and still links reproduction as a duty and act of personal fulfillment for women, resulting in the control of these bodies. Furthermore, from Sueli’s Carneiro perspective, the raciality device feeds on stereotypes, discourses and practices of coloniality that allows black women to be violated in a different, more serious and more frequently, depriving them of structures and rights to experience healthy motherhood, increasing the risk of death due to negligence in prenatal care and obstetric violence and/or denying access to legal and safe abortion. Besides, through raciality device it is verified that the production of knowledge and the constitution of powers, among which is the law, was produced by individuals and for individuals who occupy the zone of Being, a space in which black women are not inserted. Therefore because they are focused only on the dimension of choice and do not consider the confrontation of the oppressions that shape the autonomy of black women, it is said that the norm questioned is insufficient to legally protect them. On the other hand, it is proposed that this gap be filled by the theory of reproductive justice, which offers tools for the realization of reproductive rights by facing the racial barriers imposed on black women in this area. In the field of law, it works as an emancipatory tool, as it complements the doctrinal construction of these rights, training professionals who are attentive to the various types of oppression that affect the exercise of rights, encouraging the production of knowledge from the perspective of non-hegemonic bodies and highlighting problems that must be faced in the judiciary and legislative exercise.